Brand loyalty determinants of imported cosmetic brands among females in Malaysia - Tee, Wen Hui (2019)
Cosmetics have increased demand from the society due to the changing environment. Recently, imported cosmetic brands become more popular in Malaysia due to the changing of trends. The hyper competitive environment in the cosmetic industry makes it a valuable area to study brand loyalty in especially imported cosmetic brands. Brand loyalty is one of the important aspects which is significant for the companies to sustain competitive advantages in the market. In this research, the relationship between brand loyalty and determinants of brand loyalty was studied, with special focus on brand image, price, promotion, trust and perceived quality. The purpose of this research is to identify the determinants that affects brand loyalty of imported cosmetic brands in Malaysia. The data for this research was collected through survey questionnaire. The target respondents are mainly females. The respondents are sampled using the convenience sampling method. 220 sets of data were collected after distributing survey questionnaire in Malaysia and various analyses were carried out using SPSS. This research showed that brand image, promotion, trust and perceived quality have significant relationship with brand loyalty of imported cosmetic brands. This project provides managerial and theoretical implications, as well as the recommendations in order to propose beneficial suggestions for future studies.